Building aesthetic and expressive long shot in the film contemporary novelist (Al-Academy, 2017)
The research deals with an important detail of the joints of the film industry and television drama, which is the expression and aesthetic of the long shot, after being popularized by some directors, and that the long shot has been employed since the beginning of the cinema. But the research addresses the contemporary film and how the long shot worked. The researcher identified her goal in identifying the aesthetic and expressive of the long shot in the contemporary film, and then defined the term of the shot and the long shot.The theoretical framework was based on two topics: the first (aesthetic and artistic expression in cinema) and the second (the long shot and the state of its construction). The researcher then chose LA LA LAND (2016) as a sample for analysis. The research then came out with a set of conclusions and conclusions. Then the margins and sources of research and a summary in English